Meningkatkan Kualitas Hidup Pasien Hipertensi Melalui Edukasi Kolaboratif Antarprofesi Kesehatan dengan Poster "CINTA SEGAR" - Munawaroh, Siti; Koesmawarni, Aisyah; Puspita, Arum Diah; Adhirajasa, Danindra Rizq; Anggraini, Fanny; Friyantika, Firda (Abdimas Universal, 2025)
Hypertension is a chronic disease with a high prevalence worldwide, including in Indonesia. If not managed properly, it can significantly reduce the quality of life of those affected. Innovations in public education are being carried out through a collaborative approach among health professions. The community service program implemented by the collaborative team aims to evaluate the effectiveness of collaborative education in improving the quality of life of hypertension patients. This activity was carried out in Dusun Ngemplak, Desa Sambon, involving doctors and midwives. The methods used included family health assessments, education through posters, and the implementation of Interprofessional Collaboration (IPE). The results from the collaborative community service show that the education provided had a positive impact on hypertension patients, leading to an increase in knowledge and adherence to hypertension treatment. The quality of life of hypertension patients also improved as a result of the successful education provided by the interprofessional collaboration team. Interprofessional collaborative education is effective in improving the quality of life of hypertension patients. This approach can serve as a valuable model for hypertension management efforts for the hypertension patients.